Membedah Mitos Budaya Massa dalam Pilpres 2024: Tinjauan Semiotika Roland Barthes - Wattimena, Grace Heidy Jane Amanda; wukir, Iswahyu Prana (Universitas Bunda Mulia, 2024)
This research aims to dissect mass culture myths that have emerged in the context of the 2024 presidential election through a review of Roland Barthes' semiotics. The focus of this research is on the role of the media in forming and spreading myths, as well as their impact on public perception and voter decision making. The research results show that mass media, including television, radio, social media, and print media, have a crucial role in building narratives, images and symbols that contribute to the formation of mass cultural myths. Connotation analysis shows the existence of an ideological bias in these myths, which is influenced by political affiliation, economic interests, and social norms. This research also highlights the manipulation of symbols in strengthening mass cultural myths. Political actors use symbols such as flags, colors, and logos to evoke emotional responses and form associations with certain ideas or values. The impact of mass culture myths on voter decision making is very significant, because they can influence the way voters view political candidates and the policies they promote. In terms of denotation, this research emphasizes the importance of efforts from all contestants to encourage constituents to think critically, literately, and independently evaluate in making decisions based on accurate information in the democratic process. In terms of connotation, efforts to reduce the impact of filter bubble s in the 2024 presidential election, collaboration between social media users, social media companies and the government is predominantly neglected. In fact, the myth of election fraud must be confronted with constructive efforts of awareness, education, and appropriate action, so that the public can create a space for diverse political dialogue and promote better and deeper understanding.